Domestic Workers and their access to childcare: A Socio-Legal study - van Zyl, Nicole (Centre for Law and Society, 2019)
This dissertation explores how domestic workers within the Cape Town area access childcare. From this exploration, the argument that the state should provide childcare to mothers as a redress measure under s9(2) is developed. This argument is drawn from the proposition that universal access to childcare has the potential to reduce gender inequality by removing the care burden that women bear. By providing universal access to childcare, and thereby removing or reducing the care burden, women are better empowered to access income earning activity. This qualitative enquiry utilises a literature review and one-on-one interviews as modes of data collection. Eight interviews were conducted on the experiences of domestic workers. A feminist methodology was adopted in the collection and analysis of the data, which led to the finding that greater state intervention is needed into the lives of domestic workers so that they may realise substantive equality. This Constitutionally based legal analysis is used as a means of understanding social transformation through the experiences of the participant group.